SOCIAL LANDMARKS IN YURII ANDRUKHOVYCH’S PUBLICISTIC ESSAYS - Ващук, І. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article analyses the ideological tendency, socially important landmarks of Yurii Andrukhovych’s open journalism, the writer’s views on new literature and journalism, blog articles. It defines that the grounds for the author’s social-politicalideal are European values, a transparent, free and just civil society.